Express Model for Analyzing the Process of Soil Heating in a Greenhouse - Biliaieva, V. V.; Shcherbyna, S. A. (Science and Transport Progress, 2025)
Purpose. The organization of artificial soil heating in a greenhouse plays an important role in ensuring efficient plant cultivation, as the optimal soil temperature is a key factor in this process. The heating itself must be carried out in such a way as to ensure a certain temperature range in the soil, in particular in the area where the root system of plants is located. The soil heating process depends on the specific operating conditions of the greenhouse. To organize a rational and energy-saving process, it is necessary to determine the parameters of the heating system in advance, at the design stage. An effective method for solving this problem is to use mathematical models. The main purpose of the study is to develop a one-dimensional express model for evaluating the process of soil heating in a greenhouse. Methodology. The equation of thermal conductivity was used to study the dynamics of artificial soil heating. The numerical integration of the modeling equation was carried out using a finite-difference scheme of total approximation. Findings. A computer program has been developed that can be used to conduct a computational experiment to determine the dynamics of artificial soil heating in a greenhouse. The results of numerical modeling are presented. Originality. A one-dimensional numerical model for analyzing artificial soil heating in a greenhouse has been developed. The model is based on the numerical integration of the heat conduction equation and allows us to quickly determine the dynamics of the formation of thermal fields in the soil both in the case of the heating element operation and in the case of its shutdown. Practical value. The developed numerical model can be a useful tool at the design stage of artificial soil heating systems. It provides scientific justification for the parameters of heating systems and energy-efficient modes of their operation. The model allows you to quickly assess the dynamics of thermal fields in the soil both during the operation of the heating element and after it is turned off. For practical application of the numerical model, only standard input information is required. Controlling the dynamics of soil heating opens up opportunities for optimal control of the heating system operation modes.